2021
DOI: 10.1177/03635465211003074
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Allografts Provide Superior and More Reliable Surface Topography Matching Than Oblong Allografts: A Computer-Simulated Model Study

Abstract: Background: Osteochondral allograft transplantation is 1 treatment option for focal articular cartilage defects of the knee. Large irregular defects, which can be treated using an oblong allograft or multiple overlapping allografts, increase the procedure’s technical complexity and may provide suboptimal cartilage and subchondral surface matching between donor grafts and recipient sites. Purpose: To quantify and compare cartilage and subchondral surface topography mismatch and cartilage step-off for oblong and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…The current results also differ from those reported by Huddleston et al, 12 who found that overlapping plugs were better than an oblong graft for oblong defects in the MFC. The current study demonstrated similar mean surface height deviations for the MFC and LFC oblong grafts (0.59 and 0.58 mm, respectively) compared with the previous study’s MFC oblong graft (0.62 mm).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The current results also differ from those reported by Huddleston et al, 12 who found that overlapping plugs were better than an oblong graft for oblong defects in the MFC. The current study demonstrated similar mean surface height deviations for the MFC and LFC oblong grafts (0.59 and 0.58 mm, respectively) compared with the previous study’s MFC oblong graft (0.62 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…There are some distinct differences between the current study and those by Urita et al 32 and Huddleston et al 12 The 2 previous studies used computer simulation models and represented “best-case scenarios” in which a computer program analyzed the complete donor surface to determine the “best-fit” region from which to harvest the donor plugs. While the surgeon also attempts to find the “best-fit” surface in the operating room, the ability of the surgeon’s eye to determine this exact location may not be as sensitive as a computer model that uses high-resolution CT data.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The topography matching algorithm was designed according to previously used methods. 11 Each cartilage trochlear graft model was virtually superimposed onto each cartilage defect model. The least distance, defined as the shortest distance between 2 cartilage polygons, was calculated for all polygons between the graft and defect in the 3D model.…”
Section: Methodsmentioning
confidence: 99%
“…Cartilage and subchondral bone surface models were segmented and exported as polygon models, as performed in other studies. 11,[19][20][21] One specimen at a time was chosen as the recipient (defect) model, and the other remaining specimens were then evaluated as potential donors. This process was repeated until each specimen had been evaluated as the recipient (defect) model.…”
Section: -Dimensional Model Generation and Computer-simulated Articul...mentioning
confidence: 99%